EVALUATION OF Azospirillum brassilense DOSE RESPONSE ON GROWTH AND YIELD OF MINITUBERS FROM APICAL ROOTED CUTTINGS GROWN IN COCO-PEAT - Hai Chau, Mai; The Nhuan, Nguyen (Journal of Forestry Science and Technology, 2022)
Potato (Solanum tuberosum L.) is one of the most valuable crops in the world, ranked as the 4th most important food crops after rice, wheat and maize. Currently, a variety of techniques for producing potato minituber have been investigated, including soilless aeroponic, hydroponic and deep-water culture systems. However, minitubers potato production in the greenhouse from apical rooted cutting grown coco-peat under a photoperiod and nutritional - shock system is a new and creative idea. The use of diazotrophic bacteria such as Azospirillum brasilense demonstrates a positive effect on nitrogen availability, a primordial element for the development of this plant. Therefore, this study aimed to evaluate the growth and minitubers yield in a potato cultivar inoculated with A. brasilense at different doses. The experiments were conducted in controlled greenhouse on concrete raising beds with dimensions of 10 m x 1 m x 0.3 m. The study revealed that the concentration of A. brasilense at different doses significantly affected the height growth, leaves growth, leaves area growth, the average number of tubers plant-1, standard tuber and potato seed minituber yield. The treatment applied with A. brasilense at a concentration of 200 mL m-2 after planting gave the highest yield of potato minitubers (277.8 tubers m-2).